2012
DOI: 10.5505/tjb.2012.52724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Funalia trogii in heart tissue of rats exposed to deltamethrin

Abstract: electronic) 0250-4685 (printed) 239Effect of Funalia trogii in heart tissue of rats exposed to deltamethrin [Deltametrine maruz kalan sıçanların kalp dokusunda Funalia trogii'nin etkisi] Research Article [Araştırma Makalesi] Türk Biyokimya Dergisi [Turkish Journal of Biochemistry-Turk J Biochem] 2012; 37 (3) ; 239-244. Yayın tarihi 30 Eylül, 2012 © TurkJBiochem.com [ ABSTRACTObjective: Environmental exposure to deltamethrin can cause alterations in structure and function of different organs. F. Trogii, a white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…This finding came in accordance with previous studies which reported that DM significantly decreased the antioxidant defense [9,15,28,29]. Also DM intoxication caused significant increase in NO concentration [ Table-2].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding came in accordance with previous studies which reported that DM significantly decreased the antioxidant defense [9,15,28,29]. Also DM intoxication caused significant increase in NO concentration [ Table-2].…”
Section: Discussionsupporting
confidence: 82%
“…This result was agreed with [30][31][32]. Possible reasons for reduction of TAC and increases of NO might be the utilization antioxidant enzymes to challenge the prevailing oxidative stress under the influence of free radicals generated from DM and/or inhibition of enzyme synthesis by DM [28,[33][34][35].…”
Section: Discussionsupporting
confidence: 78%
“…The biological effects of repeated exposure at low dose should be considered in animal and human health as deltamethrin affects several body organs. Changes in the cardiac contractility and increased heart rate were recorded in rats received deltamethrin (Yalın et al, 2012). Prenatal exposure to deltamethrin causes persistent changes in learning, motor behavior, muscarinic acetylcholine receptor binding and blood-brain barrier permeability (Johri et al, 2006;Kung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As a consecutive result of cell injury, catalase and glutathione (GSH) levels are reduced causing inactivation of various enzymes [13] . Malondialdehyde (MDA) is the basic product of polyunsaturated fatty acid peroxidation and is quite a toxic molecule.…”
Section: Introductionmentioning
confidence: 99%